Podgurskaya I. The authorial subjectivity and its means of expression in “The story of an unextinguished moon” by B. Pilnyak - Podgurskaya I. (Philological Treatises, 2020)
This article outlines the principal means of the authorial subjectivity implementation in “The story of an unextinguished moon” by B.Pilnyak, which were stipulated with the acute social subject matter of this work. It covers a wide range of the authorial modality means – classifying from artistically implicit to journalistically pointed ones. It gives an opportunity to express the peculiarity of authorial society conception, Pilnyak’s artistic thought and his creative subject matter.